THE IMPLEMENTATION MAQASHID SYARIAH DEVELOPMENTS BY GREEN FINANCING AT FINANCIAL INSTITUTIONS INDONESIA - Lukman Hakim Siregar; Yenni Samri Juliati Nasution (Proceeding International Seminar of Islamic Studies, 2022)
The natural failure due to indifference on aspects of environmental conservation that humans do to pursue economic development now days has come to the attention of world economists by compiling a sustainable financial framework in each country through policies and cooperation in financial sector authorities with the concept of Sustainable Finance or termed Green Financing. Thus noteworthy by Islamic economics in Maqashid Sharia which lays it as the basis of a fair economic system in the face of a modern economy that has no improvised limits. This article aims to look at the application of Green Financing to Financial Institutions in Indonesia and examine its relationship by Maqashid Syariah.Keywords: Green Financing, Maqashid Syariah